(untitled) (Global Journal of Science Frontier Research, 2012)
The present investigation is concerned with the reflection and transmission of plane waves at an imperfect interface between two different swelling porous elastic media. The expression for various amplitude ratios due to the incidence of longitudinal wave in solid (PS), transverse wave in solid (SVS) are obtained for imperfect boundary and are deduced for normal stiffness, transversal stiffness and welded contact. The resulting amplitude ratios are computed and depicted graphically for a specific model. The present investigation has immense application in structural problems, geophysics etc.